Missing pieces - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2005)
Red Rock suffers a spate of "mailbox baseball" vandalism and twins Bryce and Ashley become witnesses.
4.1
3-6
Keywords: Families -- Juvenile fiction; Stepfamilies -- Juvenile fiction; Twins -- Juvenile fiction; Vandalism -- Juvenile fiction; Christian life -- Fiction; Christian life -- Fiction; Family life -- Fiction; Mystery and detective stories; Stepfamilies -- Fiction; Twins -- Fiction; Vandalism -- Fiction; Christian fiction; Christian life -- Fiction; Family life -- Fiction; Mystery fiction; Stepfamilies -- Fiction; Twins -- Fiction; Vandalism -- Fiction; Christian fiction; Mystery fiction